2010
DOI: 10.1080/10803548.2010.11076856
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Safety Climate and Work Experience

Abstract: The study examined the relationships between work experience and (a) safety perceptions, (b) work experience safety perceptions job satisfaction compliance safety management

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 56 publications
5
13
1
3
Order By: Relevance
“…48 Similar to our results, previous studies have found that safety climate perception varies between management and workers irrespective of industry. 18,19,40,49 Despite variability by respondent job position, no scores suggested a positive perception of safety climate on construction worksites. Among Hispanic construction workers, safety climate scores had a mean of 30%.…”
Section: Variability In Perception Of Safety Climatementioning
confidence: 99%
See 1 more Smart Citation
“…48 Similar to our results, previous studies have found that safety climate perception varies between management and workers irrespective of industry. 18,19,40,49 Despite variability by respondent job position, no scores suggested a positive perception of safety climate on construction worksites. Among Hispanic construction workers, safety climate scores had a mean of 30%.…”
Section: Variability In Perception Of Safety Climatementioning
confidence: 99%
“…8,[15][16][17] Safety climate is a suggested antecedent on the injury causal pathway, directly affecting safety-related behaviors. 7,13,18,19 Unlike injury rates and lost time days, which reflect workplace safety performance retrospectively, safety climate assessment is a proactive approach for improving worksite safety. 20,21 Previous studies suggest that organizations with strong safety climate scores exhibit lower injury rates than organizations with weak scores.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the risk of a woodworker having an injury on his/her first day on the job can be even 50 times higher than that of a worker with one year's work experience (Larsson, 1988). Injury risk generally decreases as work experience increases (Butani, 1988;Gyekye & Salminen, 2010). On the other hand, it has been shown that experience per se does not decrease injury frequency independent of age (Gun & Ryan, 1994).…”
mentioning
confidence: 98%
“…Furthermore, this association was not significant in Adl et al study (14). On the other hand, study of Gyekye et al indicated that the association between safety climate and work experience was significant (18). There is a significant association between marital status and regulations and safety instructions.…”
Section: Discussionmentioning
confidence: 91%